KESESUAIAN LAHAN KOMODITAS HORTIKULTURA DI DESA HATIVE BESAR KECAMATAN TELUK AMBON - Vinda V Tentua; Husein Salampessy; Johanis P Haumahu (Universitas Pattimura, 2017)
This study aimed to determine the land suitability for horticultural commodities based on physical condition data of the land, to determine the limiting factors in the field and to give recommendation to improve the land use for horticultural commodities. This research was conducted in Hative Besar Village, Teluk Ambon Sub District in September-October 2016. This research was divided into three phases: preparatory phase of research which included secondary data collection and digitizing land unit map, field research stage covering primary data collection or field checking using free survey techniques, as well as data analysis and reporting stages that will be revealed in maps and land suitability for horticultural commodities as well as recommendations for improvement of the limiting factors. The results showed that based on the actual land suitability assessment there were only five suitable plants is rambutan, gandaria, durian, duku and pineapple. Whereas based on the actual suitability of the selected land, the appropriate plants were durian, duku and pineapple. The results of the study also indicate that there were several limiting factors, namely the availability of water, the availability of oxygen, rooting media and erosion hazard that can be improved by applying soil and water conservation techniques.